Selection of honey bees tolerant or resistant to Varroa jacobsoni - Kulincevic J.M.; De Guzman L.I.; Rinderer T.E. (The varroosis in the Mediterranean region, 1997)
In 1984, several years after Varroa jacobsoni was discovered in Yugoslavia and three years before this mite was identified in the United States, a joint research project was established. The goal of the project was to attempt to select a stock of honey bees tolerant or resistant to this honey bee parasite. Three queens were collected from apiaries which had extremely high losses believed to be a result of V. jacobsoni parasitism. Four generations of two lines of honey bees (Apis mellifera carnica) were selectively propagated from these queens. The two lines were selected for high and low brood infestation with Varroa mites. Significant differences in all generations of selection showed that this characteristic was heritable, since significant portions of this genetic variation proved to be additive. Selective breeding, if organized on a wider genetic basis, should have good promise for providing the expected long-term solution to the problem of Varroa mites. Because of this characteristic and other qualities, this resistant line of bees was imported into the United States for further testing and was later named ARS-Y-C-1. Using a short test for larval attractiveness, ARS-Y-C-1 was found to be less attractive to V. jacobsoni, having lower levels of infestation than Hastings (A.m. carnica from Canada), and Louisiana stocks. Infestation of a cross between ARS-Y-C-1 and Hastings stocks was intermediate. In a field experiment, results showed that all three Carniolan stocks displayed greater tolerance to V. jacobsoni that the Louisiana stock. These stocks survived longer with higher levels of Varroa infestations both in worker brood and on adult bees. The susceptible Louisiana stock died earlier with lower levels of Varroa infestation.
Seminar on The Varroosis in the Mediterranean Region, 1996/09/22-23, Granada (Spain)